Whole-Genome Shotgun Optical Mapping of Rhodobacter sphaeroides strain 2.4.1 and Its Use for Whole-Genome Shotgun Sequence Assembly - Zhou, Shiguo; Kvikstad, Erika; Kile, Andrew; Severin, Jessica; Forrest, Dan; Runnheim, Rod; Churas, Chris; Hickman, Jason W.; Mackenzie, Chris; Choudhary, Madhusudan; Donohue, Timothy; Kaplan, Samuel; et al. (Genome Research, 2003)
Rhodobacter sphaeroides 2.4.1 is a facultative photoheterotrophic bacterium with tremendous metabolic diversity, which has significantly contributed to our understanding of the molecular genetics of photosynthesis, photoheterotrophy, nitrogen fixation, hydrogen metabolism, carbon dioxide fixation, taxis, and tetrapyrrole biosynthesis. To further understand this remarkable bacterium, and to accelerate an ongoing sequencing project, two whole-genome restriction maps (EcoRI and HindIII) of R. sphaeroides strain 2.4.1 were constructed using shotgun optical mapping. The approach directly mapped genomic DNA by the random mapping of single molecules. The two maps were used to facilitate sequence assembly by providing an optical scaffold for high-resolution alignment and verification of sequence contigs. Our results show that such maps facilitated the closure of sequence gaps by the early detection of nascent sequence contigs during the course of the whole-genome shotgun sequencing process.